The Rome Statute Impact: Challenge of Upholding Human Rights in Indonesia’s Human Rights Court - Rohman, Arif; Syafruddin, Syafruddin; Chalermsin, Panupong (Faculty of Law, Universitas Jenderal Soedirman, 2024)
This article examines the effect of enforcing gross human rights violations and the implications of Indonesia as a state that did not ratify the Rome Statute. This study is done by studying the legal basis of human rights courts in Indonesia. A doctrinal approach is used. The main legal materials used are the Human Right Court Law (2000) and human rights court decisions. The research findings indicate that the process of enforcing gross human rights violations requires integration between National Human Rights Commission as an investigator and the Attorney General's Office as an investigator. The substance of enforcing gross human rights violations is a formality because Indonesia, as a sovereign state, has the right to determine the model of enforcing gross human rights. However, in fact, there are still many gross human rights violations that cannot be resolved due to differences in perceptions of sufficient preliminary evidence. For this reason, reformulation of the Human Right Court Law (2000) is needed.